Exploration of Treatment that Taken by Older People with Hypertension in Kalirandu Village - Septian, Raditya Bagus; Binoriang, Dinastu Pudang (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Hypertension in older people happen because the result of decreased physiological function. The condition of hypertension is exacerbated by older people who didn’t undergo treatment. Important treatment is done by older people to prevent complications of the disease and reduce physical complaints. Treatment that was not done by older people or done but is not in compliance will affect the quality of life of older people. This study aims to identify treatment in older people who get hypertension disease. This research used a qualitative method with a phenomenological approach. Data was collected by interviewing, observing, and using field notes. There were 7 participants in this study who were determined using purposive sampling technique. The validity of the data used triangulation techniques. Data analysis consists of data collection, data reduction, data presentation, and conclusions. The results showed that there were 2 groups of older people, there are older people who adhered to treatment and older people who did not comply with treatment. Medicated adherent older people feel the positive effects of treatment, such as reduced physical complaints and normal blood pressure. Older people who are not adherent to treatment assumed that if taking medicine regularly can dramatically reduce blood pressure. Most of older people also use traditional medicine to optimize their level of health. The conclusion is quality of life of older people in Kalirandu Village is good, seen from: three older people who are obedient to treatment, four older people using alternative medicine to reduce blood pressure, and six older people look positively at the treatment. Suggestions for further researchers is to conduct quantitative research to see the factors that affect older people adherent to do treatment and not adhere to treatment.